Être écrivain et religieux au Siècle d'or Pedro de Ribadeneyra S.I. et le ministère de l'écriture dans la Compagnie de Jésus - Bouvier, Claire (Bibliothèque de la Casa de Velázquez, 2023)
Based on the particular trajectory of the Jesuit author Pedro de Ribadeneyra (1526-1611), both a central figure in the Society of Jesus and a renowned writer of his time, this book examines the complex relationship between writing, religious institution, and literary practices in order to interrogate the figure of the religious writer in the Golden Age. This research, which aims to revisit religious history through the prism of cultural and social history, illustrates how the Society of Jesus, a multipolar institution whose mode of articulation was based on the written word -both a means of negotiation and constant adjustment- was able to adapt continuously to become a key player in early modernity.